An Optimal Linear Control Design for Nonlinear Systems - Rafikov, Marat; Balthazar, José Manoel [UNESP]; Tusset, Angelo Marcelo (Abcm Brazilian Soc Mechanical Sciences & Engineering, 2008)
This paper studies the linear feedback control strategies for nonlinear systems. Asymptotic stability of the closed-loop nonlinear system is guaranteed by means of a Lyapunov function, which can clearly be seen to be the solution of the Hamilton-Jacobi-Bellman equation thus guaranteeing both stability and optimality. The formulated Theorem expresses explicitly the form of minimized functional and gives the sufficient conditions that allow using the linear feedback control for nonlinear system. The numerical simulations the Duffing oscillator and the nonlinear automotive active suspension system are provided to show the effectiveness of this method.
Keywords: optimal control; nonlinear system; duffing oscillator; active suspension system; chaotic attractor